Interaction of HCO+ Cations With Interstellar Negative Grains. Quantum Chemical Investigation and Astrophysical Implications - Rimola, Albert; Ceccarelli, Cecilia; Balucani, Nadia; Ugliengo, Piero (Frontiers in Astronomy and Space Sciences, 2021)
In cold galactic molecular clouds, dust grains are coated by icy mantles and are prevalently charged negatively, because of the capture of the electrons in the gas. The interaction of the charged grains with gaseous cations is known to neutralize them. In this work, we focus on the chemical consequences of the neutralization process of HCO+, often the most abundant cation in molecular clouds. More specifically, by means of electronic structure calculations, we have characterized the energy and the structure of all possible product species once the HCO+ ion adsorbs on water clusters holding an extra-electron. Two processes are possible: i) electron transfer from the negative water cluster to the HCO+ ion, or ii) a proton transfer from HCO+ to the negative water cluster. Energetic considerations favor electron transfer. Assuming this scenario, two limiting cases have been considered in astrochemical models: (a) all the neutralized HCO+ is retained as neutral HCO adsorbed on the ice and (b) all the neutralized HCO+ gets desorbed to the gas phase as HCO. None of the two limiting cases appreciably contribute to the HCO abundance on the grain surfaces or in the gas.